Jornada no plural, gênero no feminino:considerações sobre a relação entre trabalho doméstico e valor - Silva, Geice Queila de Lima (2013)
The unpaid domestic work is the object of our analysis, socially identified as the place of women, where the use of time is invisible to the "world of work". We conducted a literature review with analysis of primary data (previous research) and secondary data; traversed the theoretical- methodological way from Marx to seek the understanding of what are the ontological and contemporary work activities, revisiting how social reproduction is processed and how domestic work is set. Research results show that women work more than men in almost all societies, particularly in rural regions of so-called "developing countries", as we could observed in the State of Alagoas, and in surveys conducted by the research group Gender and Human Emancipation - CNPq. Throughout the history of private property, the activities of social reproduction were allocated to an ever more private space. In capitalism, this process has its basic core in the domestic space; that in this mode of production is separated from the production of goods. This separation characterizes the basis of the current system of sociosexual division of labor, with a sense of economic, cultural and political characters. There is unpaid domestic work useful to capital, an outsourcing of free time socially necessary to the maintenance of the offspring. Unpaid domestic work also contributes to the replacement of the commodity labor power, which plays a part in the production value of this commodity. It is a social use value that is different than the social value resulting from any form of production, which is naturalized by the patriarchal ideology. Contemporary developing societies, demonstrate current government policies of private regulation of collective demands of reproduction, called compensatory policies, deepen the locus of the house as the female space preferred. There is a “natural feminine workday”, supported ideologically by the feminization of social demands of motherhood, which must be addressed for a better understanding of the role of unpaid domestic work in the logic of capitalist exploitation.